Effect of delta (δ)-tocotrienol supplementation on the Blood Follicle-stimulating Hormone (FSH) and Luteinising Hormone (LH) levels in female mice: a preliminary study / Nael Awatif Mohamad Na’im ... [et al.] - Mohamad Na’im, Nael Awatif; Wan Ibrahim, Wan Nor Hidayah; Nordin, Massita; Mohamed, Ruzianisra; Mohd Mutalip, Siti Syairah (Faculty of Pharmacy, 2023)
One of the factors causing female infertility is the deficiency in blood follicle-stimulating hormone (FSH) and luteinising hormone (LH) levels. Both hormones are important for the maturation and growth of follicular cells and ovulation. Vitamin E first discovered in 1992 is a potent lipid-soluble antioxidant and has been reported to exert beneficial effects on the reproductive system. However, its effects particularly on the FSH and LH levels have not been widely reported. Hence, this study was conducted to determine the effect of vitamin E, particularly delta (δ)-tocotrienol supplementation on the blood FSH and LH levels in female mice. Thirty (30) female mice were divided into five groups, with 4 treatment groups supplemented with 0.1ml corn oil (G2), 10 (G3), 20 (G4) and 30 (G5) mg/kg/day of δ tocotrienol while one group without any treatments (G1 = control) for 7 days. On the 8th day, blood samples were collected and analysed using ELISA analysis. Based on the results obtained, mice treated with 10 mg/kg/day of δ-tocotrienol (G3) showed the highest blood FSH and LH levels compared to the other treatment groups. Thus, δ-tocotrienol is suggested to exert improved hormonal regulation in females, and further studies are needed to confirm the effects.